Placental Growth Factor Is Required for Ovulation, Luteinization, and Angiogenesis in Primate Ovulatory Follicles - Bender, Hannah R. (Endocrinology, 2017)
Placental growth factor (PGF) is member of the vascular endothelial growth factor (VEGF) family of angiogenesis regulators. VEGFA is an established regulator of ovulation and formation of the corpus luteum. To determine whether PGF also mediates aspects of ovulation and luteinization, macaques received gonadotropins to stimulate multiple follicular development. Ovarian biopsies and whole ovaries were collected before (0 hours) and up to 36 hours after human chorionic gonadotropin (hCG) administration to span the ovulatory interval. PGF and VEGFA were expressed by both granulosa cells and theca cells. In follicular fluid, PGF and VEGFA levels were lowest before hCG. PGF levels remained low until 36 hours after hCG administration, when PGF increased sevenfold to reach peak levels. Follicular fluid VEGFA increased threefold to reach peak levels at 12 hours after hCG, then dropped to intermediate levels. To explore the roles of PGF and VEGFA in ovulation, luteinization, and follicular angiogenesis in vivo, antibodies were injected into the follicular fluid of naturally developed monkey follicles; ovariectomy was performed 48 hours after hCG, with ovulation expected about 40 hours after hCG. Intrafollicular injection of control immunoglobulin G resulted in no retained oocytes, follicle rupture, and structural luteinization, including granulosa cell hypertrophy and capillary formation in the granulosa cell layer. PGF antibody injection resulted in oocyte retention, abnormal rupture, and incomplete luteinization, with limited and disorganized angiogenesis. Injection of a VEGFA antibody resulted in oocyte retention and very limited follicle rupture or structural luteinization. These studies demonstrate that PGF, in addition to VEGFA, is required for ovulation, luteinization, and follicular angiogenesis in primates.